Barriers to and Correlates of Retention in Behavioral Health Treatment Among Latinos in 2 Different Host Countries: The United States and Spain. Issue 1 (January 2017) - Falgas, Irene; Ramos, Zorangeli; Herrera, Lizbeth; Qureshi, Adil; Chavez, Ligia; Bonal, Covadonga; McPeck, Samantha; Wang, Ye; Cook, Benjamin; Alegría, Margarita
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Context: Latino immigrants constitute a large portion of the Spanish and US immigrant populations, yet a dearth of research exists regarding barriers to retention in behavioral health care. Objectives: To identify and compare perceived barriers related to behavioral health care among first- and second-generation Latinos in Boston, Madrid, and Barcelona, and evaluate whether the frequency of behavioral health care use in the last year was related to these barriers. Design, Setting, and Participants: Data were obtained from the International Latino Research Partnership project. First- or second-generation self-identified Latino immigrants aged 18 years and more who resided more than 1 year in the host country were recruited from community agencies and primary care, mental health, substance abuse, and HIV clinics. Main Outcome Measures: Eleven barriers were assessed and compared across sites. The relationship between barriers and behavioral services visits within the last year was evaluated, adjusting for sociodemographics, clinical measures, degree of health literacy, cultural, and social factors. Results: Wanting to handle the problem on one's own, thinking that treatment would not work, and being unsure of where to go or who to see were the most frequently reported barriers for Latino immigrants. Previous treatment failure, difficulties in transportation or scheduling, and linguistic barriers were more likely to be reported in Boston; trying to deal with mental health problems on one's own was more commonly reported in Barcelona and Madrid. Two barriers associated with the number of visits were concerns about the cost of services and uncertainty about where to go or who to see. Conclusions: After adjusting for sociodemographics, clinical measures, degree of health literacy, cultural, and social factors, barriers still differed significantly across sites. Efforts to improve behavioral health services must be tailored to immigrants' context, with attention to changing attitudes of self-reliance and outreach to improve access to and retention in care.